Combining ability, heritability, heterosis, and stability analyses of watermelon hybrids - Mohd Masaruddin, Bahari (2012)
An evaluation on watermelon hybrids derived from a complete 4 x 4 diallel crosses were conducted at two locations, MARDI Bukit Tangga Research Station, Kedah and MARDI Seberang Perai Research Station, Penang with two planting seasons at each location. Objectives of the study were to identify the superior and highly stable F1 watermelon hybrid for yield and fruit quality, to estimate the combining ability of inbred lines in a complete diallel cross, to determine the genetic control and heritability of important traits in the watermelon population and to quantify and determine the level of heterosis revealed by the F1 hybrids. Results from evaluation across environments of the watermelon genotypes showed that inbred line CS-19 had longest vine length, thickest rind and heaviest fruit weight among all genotypes, whereas inbred line BL-14 was earliest in flowering and inbred CH-8 was best for the earliest in days to fruit maturity. Meanwhile hybrid CH-8 x CS-19 had the highest fruit yield per plant compared to other genotypes. Analysis of combining ability among the four watermelon inbred lines showed the presence of both additive and non-additive gene effects in each environment as well as across environments. However, the additive gene effects are more important than non-additive gene effects since the mean squares for general combining ability (GCA) were greater than the mean squares for specific combining ability (SCA). Inbred line CS-19 was the best general combiner ability for vine length, fruit yield, fruit weight and number of fruits, while inbred line BL-14 was the best general combiner for days to flower and days to fruit maturity. Inbred line 6372-4 was best general combiner for flesh colour, while inbred line CH-8 was the best general combiner for total soluble solid contents. The hybrids that showed significant SCA effect were BL-14 x 6372-4 for rind thickness, fruit yield and fruit weight, CS-19 x CH-8 for days to flower, flesh colour and fruit weight; CS-19 x 6372-4 only for fruit weight and BL-14 x CH-8 only for flesh colour. The environment has a significant influence on the magnitude of correlation coefficients for some of the traits studied. In hybrid populations, fruit yield was highly correlated with vine length, rind thickness and fruit weight at all environments. In general, the hybrids exhibited low to moderate heterosis values for most of the traits. However none of the hybrids had heterosis over better-parent for days to flower, days to fruit maturity and flesh colour traits. Hybrid 6372-4 x BL-14 had moderate heterosis over mid and better-parent for fruit yield. The estimates of broad- and narrow-sense heritability values were generally low at each environment as well as across environments. Days to fruit maturity showed moderate broad-sense (30%) and narrow-sense heritability (33%) estimates compared to other traits. Through combined used of the five stability statistics, hybrid BL-14 x 6372-4 was identified to be highly stable for vine length, days to flower, days to fruit maturity, total soluble solids content and fruit yield, while hybrid CS-19 x 6372-4 was highly stable for fruit weight. These superior hybrids will be recommended for commercial cultivation after multi-location trials and large scale evaluations have been done in the future.